The ratio of dietary diversity score versus energy density in relation to anthropometric and biochemical variables among patients with chronic kidney diseases - Rouhani, Mohammad Hossein; Mortazavi Najafabadi, Mojgan; Moeinzadeh, Firouzeh; Azadbakht, Leila (Progress in Nutrition, 2019)
Background: Some evidence showed that dietary diversity score (DDS), a diet quality index, was not always related to healthy outcomes. It seems that DDS to energy density ratio (DDS/ED) can overcome limitations of DDS. The aim of current study was to assess the association between either dietary DDS or DDS/ED and nutrient intake, anthropometric and biochemical measures in subjects with chronic kidney disease (CKD). Methods: Two hundred seventy patients with CKD were randomly selected for this cross-sectional study. Dietary intakes were assessed using a 168-item semi quantitative food frequency questionnaire. Moreover, anthropometric indices, lipid profile, blood urea nitrogen (BUN) and high sensitivity C-reactive protein were measured. Results: Body mass index (BMI) had a significant negative trend across quartiles of DDS and DDS/ED. Also, a negative trend for waist circumference was observed across quartiles of DDS/ED. Although the trends of selenium (P<0.01) and niacin (P=0.03) were significant across the quartiles of DDS, higher nutrient adequacy ratios for all important nutrients were observed among those in the top quartile of DDS/ED compared to the lowest quartile. We observed a significant trend of mean adequacy ratio just across quartiles of DDS/ED. Compared with the top quartile of DDS/ED (not DDS), the risk of overweight/obesity in the lowest quartiles was higher in adjusted model (P<0.001). The trend of the risk of elevated lipid profiles, BUN and hs-CRP across quartiles of DDS/ED and quartiles of DDS was not significant. Conclusion: Our results showed that DDS/ED corrected the failure of DDS in relation to risk of obesity. Moreover, it was observed that DDS/ED was better indicator of nutrient intake in comparison with DDS among patients with CKD. It is suggested that future studies use DDS/ED instead of DDS. Also, in clinical practice, dietitians should emphasize on diversity in low energy-dense food groups.